Peningkatan Hasil Belajar IPA Melalui Model Pembelajaran Think Pair Share (TPS) Berbantuan Media Telepon Kaleng Sederhana - Sri Rochmayanti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aimed to determine the improvement of in science learning outcomes throughthe Think Pair Share model using Canned Telephone Media for Grade IV students of SDNTegalrejo in the academic year of 2019/2020. The study was classroom action researchconducted in two cycles. Each cycle consisted of planning, acting, observing, and reflecting.The subjects were 30 fourth grade students at SDN Tegalrejo. The data collection resultswere analysed using the test. The test results were analysed by descriptive-quantitative technique. It showed that there was an improvement in learning outcomes from the Pre-cycle by an average of 58.6 with a percentage of the MMC value of 40%. The Cycle I was 77.2 by a percentage of the MMC value of 70% and Cycle II was 89.7 by a percentage of theMMC value of 96.6%. The results indicated that science learning using the Think PairShare model using Telephone Cans Media can improve the learning outcomes of fourthgrade students of SDN Tegalrejo in the academic year of 2019/2020.